Models of polarized and variable radio emission in the IDV source 0917+624 - Beckert, T; Kraus, A; Krichbaum, T; Witzel, A; Zensus, J (2002)
We examine the power spectrum of intra-day variability and describe the new information which can be derived from wavelet analysis of light curves of the quasar 0917+624. Results for total and polarized flux at 11 cm are shown. Both interstellar scattering and intrinsic models have difficulties in explaining the similar to 1 day period variations. A theoretical model for the time-averaged emission is presented. This provides a basis for the analysis of possible variations.